The Effect Of Limestone and Fly on Clay Stabilization of CBR and Soil Compressive Strength - Syafwandi, Syafwandi; Lonarissa Harditya Putri, Vandika Nadia; Karsono, Bambang (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
The subgrade is the road access construction project must have a firm soil bearing capacity to withstand its load. Clay soil has high water content and expands quickly. Various ways have been done to overcome it; one is improving the original soil properties using the stabilization method. The research was conducted to stabilize expansive clay soil using fly ash and limestone with a percentage of fly ash of 5%, 10%, 15%, 20% fly ash, and 25% limestone. Existing soil was used from a good pad construction project in Ujung Pangkah, Gresik, East Java. The tests carried out are specific gravity, Atterberg, compaction, CBR, and UCT tests. The CBR test was conducted to determine the appropriate CBR value to support DDT. The compressive strength of the soil was tested using the UCT test. The study results of the effect of fly ash and limestone are an increase in the dry weight of the earth and a decrease in soil water content. The rise in CBR and maximum soil compressive strength with a mixture variation of 20% fly ash + 25% limestone, Qu is 2.98 kg/cm 2, and CBR is 10.56%. This is due to a decrease in the water content, thereby increasing the dry weight of the soil.